Contemporary results of human microbiome studies with particular emphasis placed on the oral microbiome and its role in etiopathogenesis of periodontitis - Wiernicka-Menkiszak, Maria; Dembowska, Elżbieta; Kozłowska, Beata (Journal of Stomatology, 2018)
In 2005 a broad scale project on human microbiome research (the Human Microbiome Project – HMB) was initiated. Its aim was to research the composition of the microflora of the human body, and create a genome database of microorganisms existing on the human body surface and having contact with the external environment. The scope of the project involved examining oral microbiomes of 250 healthy individuals at reproductive age. As a result, an extensive database of bacterial genomes was created and variabilities dependent on the examined environment, race, sex, ethnicity, and eating habits were determined. The aim of this paper is to present the contemporary state of knowledge on the composition of micro¬organisms populating the human body with a special emphasis placed on the composition of oral microflora and subgingival biofilm, and including comments regarding phylogenetic adaptation of humans to life in the world of micro- organisms. Contemporary methods of microorganism identification significantly broaden our knowledge on the composition of microflora in various biotopes, and correlations of microorganisms in different ecosystems as well as among each other. However, the knowledge is still fragmented and fails to provide a firm basis to introduce advantageous and permanent changes in the microbiome. Yet, it allows for verifying some hitherto accepted theories regarding the role of bacteria in health and sickness. Thanks to the above, in periodontology views on etiopathogenesis of periodontitis have been changing. The contemporary state of knowledge on the human oral microbiome is becoming broader and broader. It may lead to discussions about changing some hypotheses regarding the role bacteria play in periodontitis; however, there are too many unknowns to provide bases for pharmacological or biological changes in its composition.